To solve the system of equations using the substitution method, we have the following two equations:
- \( 3x + 5y = 9 \)
- \( x - 2y = 3 \)
First, let's solve the second equation for \(x\):
\[ x = 2y + 3 \]
Now substitute this expression for \(x\) into the first equation:
\[ 3(2y + 3) + 5y = 9 \]
Distribute the 3:
\[ 6y + 9 + 5y = 9 \]
Combine like terms:
\[ 11y + 9 = 9 \]
Subtract 9 from both sides:
\[ 11y = 0 \]
Now, divide by 11:
\[ y = 0 \]
Now that we have \(y\), we can substitute it back into the expression we found for \(x\):
\[ x = 2(0) + 3 = 3 \]
So the solution to the system is:
\[ x = 3, \quad y = 0 \]
Now, let's check the solution by substituting \(x\) and \(y\) back into the original equations:
- Check \(3x + 5y = 9\):
\[ 3(3) + 5(0) = 9 \rightarrow 9 = 9 \quad \text{(True)} \]
- Check \(x - 2y = 3\):
\[ 3 - 2(0) = 3 \rightarrow 3 = 3 \quad \text{(True)} \]
Both equations hold true, so the solution \( (x, y) = (3, 0) \) is correct.
Thus, the final solution is:
\[ \boxed{(3, 0)} \]